Security fundamentals - Bryan, Wes; Deal, Lauren (Packt Publishing, 2024)
The course begins with foundational security principles, introducing you to the landscape of digital threats, vulnerabilities, and the mechanisms behind cyber exploits. It delves into the importance of understanding and mitigating risks to minimize their impact on organizations and individuals. The course focuses on both the human and technical aspects of security, ranging from social engineering and physical security measures to the intricacies of browser and wireless security. It emphasizes the criticality of robust user authentication methods, comprehensive permissions, and stringent password policies to fortify defenses against unauthorized access. The course wraps up by exploring advanced concepts such as encryption, secure protocols, and network isolation, equipping you with the knowledge to implement effective security strategies and solutions. Throughout this journey, you'll gain insights into the significance of each topic in protecting information assets and ensuring the integrity of digital environments. What you will learn Understand core security principles Identify and mitigate digital risks Combat social engineering tactics Implement strong password policies Secure networks with firewalls Protect against malware threats Audience This course is ideal for IT professionals, system administrators, and cybersecurity enthusiasts seeking to bolster their knowledge of digital defense mechanisms. A fundamental understanding of computer networks and internet functionality is recommended. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Wes Bryan: Wes Bryan embarked on his IT career path in 2009, initially as a mentored learning instructor, and later transitioning into a technical IT instructor. His exceptional teaching skills were recognized with three global teaching awards for 'Global Technical Instructor' during his early teaching years. Wes has made notable contributions as a member of the CIN (CompTIA Instructor Network) Advisory Board and the Board of Directors for CompTIA AITP (Association of Information Technology Professionals). Certifications: CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+; MCSA; MTA; MCTS; MCP; MS; MCT. Lauren Deal: With a decade of in-classroom teaching experience, work as a national television host on the Home Shopping Network, and a background as a talk show producer and host, Lauren Deal possesses a perfect blend of skills and interests in IT. This unique combination makes her an ideal learner advocate for ACI Learning training. She excels in asking clarifying questions related to exam objectives and enthusiastically learns alongside ACI Learning audiences. Additionally, Lauren has been studying the evolving use of AI technology and the development process of Augmented and Virtual Reality. Her certifications include AWS Certified Cloud Practitioner.
Online resource; title from title details screen (O'Reilly, viewed February 27, 2024)
Keywords: Computer security; Sécurité informatique; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet